PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENELANTARAN ANAK DI WILAYAH KEPOLISIAN RESOR KOTA PEKANBARU - Mery Natalia Siahaan; Dessy Artina; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In article 76 B of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection states that the criminal act of neglect of children is punishable by imprisonment of up to 5 (five) years and / or a maximum fine of Rp. 100,000,000, - (one hundred million rupiah). A short sentence of 5 (five) years imprisonment cannot be mediated because the threat of a minimum sentence of 5 (five) years in prison is a category of serious criminal offense, but in fact, in the Pekanbaru City Police, there are many cases of neglect that have not been resolved because the investigation was terminated by the party. Police due to mediation. In this case, it can be said that the law enforcement carried out by the Pekanbaru City Police has not been maximized so that it does not provide a deterrent effect on perpetrators and communities who commit acts of child neglect.This type of research is sociological legal research, namely as an attempt to see the effect of the enactment of positive law on people's lives. This research is also descriptive in nature, namely the author tries to provide a description of law as a social control related to the formation and maintenance of social rules to law enforcement officials and the community, by providing a basis for the legal ability to control behaviors and create a suitability and comfort in society ..The results of this study are to explain that the law enforcement carried out by the Pekanbaru City Police, especially the Women and Children Protection Unit Investigators, has not been maximal in the criminal case of child neglect. The obstacle factors faced by the Police are the lack of quality and quantity of the Women and Children Unit Investigators, the lack of cooperation between victims or victims' families in providing information regarding cases of child neglect that are being processed, while the dominant factors as obstacles are community factors, economic factors. and cultural factors, and a lack of awareness in understanding the law for the community. The efforts that the authors offer in this study are to improve the quality and quantity of investigators of the women and children unit in the Pekanbaru City Police, to increase public insight regarding the importance of legal awareness in order to create justice, benefit and general welfare.Keywords : Law Enforcement - Crime - Neglect – Children